Characterization of collagen extract from the skins of commercial freshwater fish - Anida Aminudin; Shamsul Mohammad; Ruhil Hayati Hamdan; Rumaizi Shaari; Mariam Firdhaus Mad Nordin; Roselina Ahmad Saufi; Soon Jan Mei
Collagen was documented as a difficult and expensive protein to quantify due to its insoluble. It is particularly since solubility is a key functional property in a variety of applications such as healthcare and cosmetic products. The main aim of this study was to extract the collagens from the skins of commercial freshwater fish such as red tilapia (Oreochromis niloticus), catfish (Clarias gariepinus) and pangasius (Pangasius pangasius) together with characteristics defined for each type of collagen extraction. The extracted collagens were determined in their molecular weights by using SDS-PAGE and the structure of it was observed under SEM. The obtained molecular weight of all three commercial fish collagens is approximately >80kDa. The characteristics of each type of collagen were then defined by using appropriate analysis through this research.